(untitled) (Archives of Criminology, 1991)
The object of the paper is to show the trends of convictions for aggressive offences in Poland in the years 1972-1987 basing on court statistics, and to characterize this type of offences and their perpetrators. Moreover, basing on the findings of several Polish criminological studies, some of the factors have been indicated which may play an important part in the origin of aggressive offences. The main focus here is the problem of such offenders aggressiveness and their drinking habits, as the two factors are rather clearly connected with the discussed type of offences. Offences to be submitted to statistical analysis have been separated according to psychological and criminological criteria and not to the classification adopted in the Polish penal code. Thus only those offences from various chapters of the penal code have been taken into account where the facts of the given cases contained an explicit element of physical aggression against person or object, or of verbal aggression. Naturally, there is a great variety of acts which contain an element of aggression and are numbered among offences: they infringe different human values and interests from as vital as life and health to dignity, honour, or religious feelings. Also different is the seriousness of those acts (both misdemeanours and crimes being found among them), as well as the danger they create to the public weal, and the statutory penalties provided for them. Throughout the analysed period 1972–1987, the total number of convicted persons was relatively stable and amounted to the average of 150–160 thousand a year; it went down in 1977 and 1981–1984, only to increase again to the previous level in the years 1985–1987. Also the crime rate fluctuated similarly, amounting to 65–59 per 10,000, adult population, with the exception of 70.6 in 1972. In some years, the decrease of both the number of convictions and the crime rate can be explained with amnesty laws, while the increased number of convictions, in the years 1985–1987 resulted, among other things, from certain additional though temporary legal regulations introduced in that period (particularly from the Act of 1985 on special criminal responsibility). In the period under analysis, the proportion of persons convicted for aggressive offences amounted to about 40 per cent of the total number of convictions. At the same time, starting from 1975, a certain slight downward trend in the proportion of such convictions can be found, to as low as 35-36 per cent in the years 1979–1980, followed by an increase to the previous level. A certain decrease in the extent of convictions for aggressive offences can be explained partly with demographic changes. In the period under analysis, despite the general increase of the population aged 17 and more (by 12.9 per cent), the number of men aged 17–20 went down by about 35.5 per cent, and the same trend could be found in the case of men aged 21–24. It is a well-known fact that aggressive offences are committed mostly by young persons. Analysing the extent of aggressive offences from the point of view of the offenders’ sex and age, we find somewhat different trends in young adult as compared with adult men and women. Aggressive offences constitute about 60 per cent of all offences committed by young adult men, and 34–40 per cent of those of adult men. In the period under analysis, offences of this type committed by young adult men kept up the above level, fluctuations being greater in the case of adult men. In the structure of female crime, aggressive offences play a less significant role and constitute about 20 per cent in both age groups. There is also, as in the case of men, a distinct trend: stability of proportion of convictions of young adult women for such offences (about 20 per cent), and a distinct decrease in the case of adult women (from 23 to 12.6 per cent). Taking certain groups of offences as well as the separate acts into account, we find a considerable increase in the number of aggressive offences against property. It is determined mainly by the increase in the proportion of convictions for burglary and of particularly audacious larceny, and to a slight extent – for damage to property. Instead, proportions of convictions for robbery are rather stable. In the discussed period, robbery which contains an explicit element of aggression revealed no changes as regards the number of convictions: instead, upward trends could be found mainly in the case of burglary and of particularly audacious larceny where explicit aggressive traits can not always be found. Thus this finding corresponds but to some extent with the world trend. In the discussed period, a downward trend could be found as regards convictions for offences which involved physical and verbal aggression against person. Convictions for offences traditionally regarded as serious and dangerous for the public weal, such as murder or rape, remained at the same level, while those for bodily injury trended downwards. As has been mentioned above, the number of robberies, also included among serious offences, remained stable, the proportion of convictions for offences of this type arnong all convictions for aggressive acts being rathen low (murder, 0.5–07 per cent; rape, 2 per cent; robbery, 6.8 per cent). What should also be stressed is the decrease in convictions for participation in a brawl or battery, particularly in rural districts, and for assault on a public functionary or police officer, starting from 1978. Instead, convictions for physical or moral cruelty towards a family member maintain a rather high level with a slight upward trend. A regular increase it the number of convictions for that offence which dates from 1950s, is related to the trends in prosecuting and sentencing policy in family cases. The influence of the changes in criminal policy and legislation is also distinct in the case of convictions for violation of bodily inviolability, insult, and insult of a police officer which went down to begin with and then started increasing in numbers. The second part of the paper contains a discussion of the problem of conditions of aggressive crime. An attempt was made basing on the findings of criminological studies to answer the question whether most perpetrators of aggressive offences can be characterized as highly aggressive persons and excessive drinkers. The analysis concerned both the fact of repeated perpetration of aggressive offences, and the occurrence of aggressiveness as a permanent personality trait. As may be concluded from the studies of offences committed by different samples of young adults those in whose criminal career was at least one aggressive offence (c.g.) robbery, hooligan act, homicide) were more frequently than others convicted for aggressive offences. Thus the question should be answered whether most of the perpetrators of aggressive acts are characterized by distinct aggressiveness as a permanent personality trait. One can hardly suppose in this connection that a single aggressive offence might constitute a sufficient proof of the offendner’s aggressiveness. If, however one and the same person repeatedly commits aggressive offences, he might be an aggressive individual. A person has been defined as aggressive who reveals aggressive behaviour or a decidedly hostile attitude towards many persons in different situations. It has been found basing on psychological examination with the Buss- Durkee questionnaire and detailed data from interviews (which the authoress used to construct scales of aggressiveness), that most perpetrators of aggressive offences are characterized by a considerable aggressiveness as a relatively stable personality trait. Moreover, aggressiveness measured this way is a significantly less frequent characteristic of young adult offenders against property, and of non-delinquent youth. The above findings contribute but to some extent to the explanation of the nature of aggressive crime, as aggressiveness of offenders should be considered in connection with many other factors which exert a mutual influence on one another and jointly determine a criminal act in a given situation. In studies of various samples of aggressive offenders, their considerable excessive drinking was found. The issues under analysis included, among other things, the role of drinking in the origin of aggressive crime, alcohol’s direct as well as indirect influence on criminal behaviour taken into account. It was arqued that the offender’s intoxication plays a greater part in the origin of aggressive crime than of offences against property. Also the interdependence between aggressiveness and excessive drinking. As shown by the findings (among other things, of studies of young adult perpetrators or robbery and hooligan acts), excessive drinkers revealed intense aggressive behaviour significantly more often than those who did not drink excessively; moreover, such behaviour was found already at school which means that those persons were already aggressive as children, before they developed excessive drinking habits. Theorefore, their subsequent regular drinking could have been related to emotional instability with which also their aggressiveness was connected. They could have seeked relief of their emotional tension in excessive drinking. Also aggressive behaviour served to abreact that tension. To conclude, it should be stated that the perpetrators of aggressive acts, as opposed to those who commit mostly offences against property, are highly aggressive as a rule. Most of them also regularly drink excessively. Though they were not found to be significantly different in this respect from offenders on the whole, nevertheless alcohol no doubt plays an important part in most of their aggressive acts. In a given situation, their excessive drinking habits, intoxication at the moment of the act, or aggressiveness caused or intensified their already existing serious conflicts with the environment, influenced their distorted perception and interpretation of the reality, and facilitated an impulsive reaction to casual misunderstandings, and could therefore contribute to the emergence of aggressive acts qualified as offences.